SOLUSI PERMASALAHAN DALAM KEGIATAN PERKANTORAN DI KANTOR DESA TRIHARJO DAN TRIMULYO, SLEMAN, D.I. YOGYAKARTA - Sumarto, Rumsari Hadi; Suyati, Demetria Tri Adri (Universitas Negeri Yogyakarta, 2015)
The main argument of this community service is that office work as theservice in the government bureaucracy in the urban village is an action givingimportant contribution in improving the performance of the government bureaucracytopublicserviceandperforminggoodimagetothesociety.The priorities of the problem in the implementation of knowledge andtechnology for the society toward the office work in the urban village of Triharjoand Trimulyo, Sleman, DIY are the non-standard composition of the Indonesianletters, filling, the non-standard composition of minutes, and the problemsincommunicationbyphoneorinreceivingguest.Therefore, the implementation of the knowledge and technology for thesociety focuses on helping finish the priority problems in the office work in theurban village. It aims at fixing office work either through training or correctingthe office work so that it is suitable with the standard and improves the organization'simage through the service of the office work. The significant outcomeand recommendation of the community service of the knowledge and technologyforthesocietyisthestandardizedcorrespondence,standardizedfilingsystem,rightminutes,rightandpoliteetiquetteofreceivingguestandphonecalls.The result of this community service can be one of the inputs andcontributions for the office work in other urban villages and contributions forthe office work in other urban villages so that service quality of the office workcan be more optimum